Stacking punishment: the imposition of consecutive sentences in Pennsylvania - Galvin, Miranda A. (Criminology & public policy, 2022)
Research Summary This study introduces the decision to impose consecutive sentences as a "window of discretion" in modern sentencing regimes that has the potential to produce extreme and disparate punishment. Among cases sentenced in Pennsylvania between 2015 and 2019, consecutive sentences were present in more than 20% of all cases, including 35% of cases resulting in a primary sentence to prison and 39% of cases resulting in a primary sentence to jail. The length of consecutive incarceration and probation often exceed primary sentence length and substantially extend justice involvement. Policy Implications In the absence of guidance, consecutive sentences undermine policy efforts at uniformity and correctional control. Further, relatively common use of (long) probation tails may contribute to "mass probation." Such decisions should be deserving of the same consideration as given the imposition of primary sentences, meaning the promulgation of guidance regarding imposition and reasonable limits for length.